The Fable of the Living Dead: Determinants of Corporate Mortality Present In Micro and Small Active Enterprises - de Araújo, Felipe Emidio; de Morais, Fábio Rogério; Pandolfi, Edgar de Souza (REGEPE Entrepreneurship and Small Business Journal, 2019)
This study analyzes the presence of determinants of business mortality in active Micro and Small Enterprises (MPEs). The main objective of the study is to identify the determinants of corporate mortality in the literature, recognize the presence of these factors in active companies and examine the causes of corporate survival in firms where these determinants of mortality are present. In response to the research problem, it was used a Likert scale for data collection, and conducted a comparison of mean between groups, confirmatory factor analysis (CFA) and linear regression, for the confirmation or rejection of hypotheses. We collected data in 94 MPEs located in a city in the north of Brazil, in order to compare theoretical evidences with the empirical results on the determinants of business mortality in active companies. Previous studies point out that these determinants are concentrated in three factors responsible for the mortality (entrepreneur, company and environment). Thus, if the determinants of MPEs mortality are present in active companies, which are the reasons that keep them alive? The confirmation of the hypotheses allows us to state that, in this sample, the presence of determinants of corporate mortality in active companies involves a compensation system, in which the presence of a variable with determinant level of mortality is balanced by another variable with determinant level of success. This system of compensation between the variables is relevant for the company’s survival.